Deteksi dan Identifikasi Cendawan Endofit Trichoderma yang Berasosiasi pada Tanaman Kakao - Rina Sriwati; Tjut Chamzurni; Sukarman Sukarman (Fakultas Pertanian, Universitas Syiah Kuala, 2011)
Detection and Identification of Endophyte Trichoderma Fungi Associated Cocoa PlantABSTRACT. The endophytic fungi are non pathogenic fungi and almost all of them associated with plant cells without any symptoms. Endophites fungi that associated with cacao plant from East Aceh has been isolated. Based on morphological and molecular identification was found two species of fungi Trichoderma spp which is fungal antagonist. Molecular identification have provided the species of Trichoderma virens and Trichoderma longibrachiatum. Trichoderma virens had goog poteny as biological control agains patogen.